Enhancing the Literacy of Shariah Financial Technology for Generation X, Y and Z in Indonesia - Fauzia, Ika Yunia (Jurnal Minds: Manajemen Ide dan Inspirasi, 2020)
This research tries to improve financial literacy through sharia fintech, especially in payment gateway, peer to peer lending, and crowdfunding. It focuses mainly on how the X, Y, and Z generations may improve financial literacy. The research uses a qualitative approach in analyzing its case study, involving 30 informants in Indonesia who have the knowledge or other ways and access sharia fintech. The research will then select 30 informants and ten people to represent each X, Y, and Z generations. The research shows that X generations are more literate in sharia fintech than Y and Z generations to disseminate and spread sharia fintech and improve its infrastructures and services in its products.